Perjalanan Sejarah Masa Kekhalifahan dalam Membangun Dunia Islam - M. Bimo Putra Pratama; M. Rizki Hidayatullah; Hudaidah Hudaidah; Risa Marta Yati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the historical trajectory of the caliphate period and its role in shaping the Islamic world through leadership, governance, social development, and territorial expansion. Using a qualitative literature-based approach, the research analyzes the era of the Khulafaur Rasyidin as a foundational phase that integrated theological principles with practical state administration. The findings reveal that the caliphate functioned not only as a political institution but also as a moral framework that emphasized justice, accountability, education, and social welfare. Internal conflicts and external challenges during the caliphate period are interpreted as historical realities that contributed to institutional maturity and ethical reflection in Islamic leadership. Territorial expansion facilitated cultural interaction and the dissemination of Islamic values, strengthening the formation of a cosmopolitan Islamic civilization. The study argues that the legacy of the caliphate remains relevant for contemporary Islamic societies, particularly in addressing leadership ethics, social cohesion, and governance challenges. Understanding this historical experience provides critical insights for contextualizing Islamic civilization as a dynamic and adaptive process rather than a static historical ideal.